Gene expression changes in spinal motoneurons of the SOD1(G93A) transgenic model for ALS after treatment with G-CSF - Henriques, Alexandre (Front Cell Neurosci, 2015)
Background: Amyotrophic lateral sclerosis (ALS) is an incurable fatal motoneuron disease with a lifetime risk of approximately 1:400. It is characterized by progressive weakness, muscle wasting, and death ensuing 3–5 years after diagnosis. Granulocyte-colony stimulating factor (G-CSF) is a drug candidate for ALS, with evidence for efficacy from animal studies and interesting data from pilot clinical trials. To gain insight into the disease mechanisms and mode of action of G-CSF, we performed gene expression profiling on isolated lumbar motoneurons from SOD1(G93A) mice, the most frequently studied animal model for ALS, with and without G-CSF treatment. Results: Motoneurons from SOD1(G93A) mice present a distinct gene expression profile in comparison to controls already at an early disease stage (11 weeks of age), when treatment was initiated. The degree of deregulation increases at a time where motor symptoms are obvious (15 weeks of age). Upon G-CSF treatment, transcriptomic deregulations of SOD1(G93A) motoneurons were notably restored. Discriminant analysis revealed that SOD1 mice treated with G-CSF has a transcriptom close to presymptomatic SOD1 mice or wild type mice. Some interesting genes modulated by G-CSF treatment relate to neuromuscular function such as CCR4-NOT or Prss12. Conclusions: Our data suggest that G-CSF is able to re-adjust gene expression in symptomatic SOD1(G93A) motoneurons. This provides further arguments for G-CSF as a promising drug candidate for ALS.